Living in the Past, Living with the Ghosts: Trauma and Postmemory in Jonathan Lichtenstein’s Memory - Tuğba Aygan (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
The 'memory boom' has promoted a wide array of plays among a large amount of literary output in Western literature. Among these, Jonathan Lichtenstein’s 2006 play Memory is an aptly named memory play. Inspired by the memories of the playwright’s father, the play interweaves three stories: one set in 1933, when the Nazis took power in Berlin; the second in East Berlin, 1990, just after the fall of the Berlin Wall; and the last in Bethlehem, 2006, as the Apartheid Wall was rising. Whilst connecting these separate stories at the intersection of memory, this paper seeks to address a traumatized and conflicted relation to the past, and drawing on established trauma theorist Dominick LaCapra’s terms ‘acting out’ and ‘working through’, it discusses how traumatic memories and one’s relation to them shape the present. The study then reflects on Marianne Hirsch’s term ‘postmemory’ as manifested in Memory as well as Lichtenstein’s life.